Chiron and the Machines of Loving Grace On Optimism, Pessimism, and Singularity - Giordano, John T. (2021)
Singularity has been a concern of the developers of cybernetics and artificial intelligence (AI) since the pioneering writings of such thinkers as Norbert Weiner. Yet many accept the inevitability of systems of AI surpassing human control and are optimistic that machine intelligence will harmonize human life with our environment. This essay examines this optimism against a reading of two poets: Richard Brautigan and Friedrich Hölderlin, these readings, it will attempt to show that the eclipse of nature by human beings can be used to examine the eclipse of the human being by machine intelligence. Thus, what is missing in machine intelligence is a dimension related to the experience of pain and joy to reconnect us in a reflective way to what has been severed or lost in the movement of humanity through history. This demonstrates that the very categories of optimism and pessimism concerning the future of AI points to the value of life, one that can never be encoded into our machines.
Keywords: Artificial Intelligence; Singularities (Artificial intelligence); Cybernetics; Human-computer interaction; Hölderlin, Friedrich; Brautigan, Richard; Optimism; Pessimism